Laryngeal Electromyographic findings in patients with vocal fold motion asymmetry. (3rd June 2016) - Woo, Peak; Isseroff, Tova F.; Parasher, Arjun; Richards, Amanda; Sivak, Mark
Abstract : Objectives/Hypothesis: Vocal fold motion asymmetry (VFMA) is often attributed to vocal fold paresis or an anatomical variant. Although laryngeal electromyography (LEMG) may be used to evaluate patients with vocal fold paresis, electrodiagnostic findings in VFMA have not been well defined. Study Design: Review of a case series Methods: Twenty‐five symptomatic patients with VFMA were examined by LEMG, and the findings were analyzed. Results: Although all were thought to have unilateral recurrent laryngeal nerve paresis, LEMG showed only nine to have unilateral recurrent nerve paresis. There were nine with both ipsilateral recurrent laryngeal nerve and superior laryngeal nerve paresis, four with bilateral paresis, and three were normal. Reduced total number of units, reduced recruitment, motor units firing fast, and polyphasic units were more common, whereas fibrillation potentials, fasciculation, positive sharp waves, and complex repetitive discharges were uncommon. The LEMG findings are most consistent with old, healed neuropathy. McNemar's test for the acute versus chronic denervation potentials showed significant differences. Conclusions: VFMA has a high incidence of vocal fold paresis that can be better defined by LEMG. The site and side of paresis is often wrong based on laryngoscopy findings alone. The LEMG findings of VFMA appear to be consistent with old, healed neuropathy Level of Evidence: 4 Laryngoscope, 126:E273–E277, 2016